Assessing Bone Mineral Density in Medical Students of Pakistan: Unveiling the Impact of Lifestyle Factors on Skeletal Health: a cross-sectional study - Kulsoom, Afifa; Noor, Mehreen; Naeem, Eeman; Noreen, Khola; Mansoor, Muhammad Umar; Mahmood, Tahir (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the frequency of low bone mineral density (BMD) and its association with lifestyle factors among medical students in Pakistan. Methods: A cross-sectional study was conducted at Rawalpindi Medical University between January and June 2025. A total of 190 undergraduate medical students were included using non-probability consecutive sampling. BMD was assessed using Quantitative Ultrasound (QUS) of the calcaneus, with T-scores recorded for each participant. Data on demographic details and lifestyle factors including physical activity, dietary intake, BMI and screentime were collected through a structured questionnaire. Statistical analysis was performed using SPSS 26.0. Pearson correlation and chi-square tests were applied with p-values ≤ 0.05 considered statistically significant. Results: Among 190 participants, 184 (96.8%) were female with a mean age of 22.08 ± 1.15 years. QUS revealed that 36 students (18.9%) with normal bone mineral status, 140 (73.7%) with osteopenia, and 14 (7.4%) with osteoporosis. QUS revealed that 36 students (18.9%) had normal BMD, 140 (73.7%) had osteopenia, and 14 (7.4%) had osteoporosis. A significant positive correlation was observed between BMI and T-score (r = 0.330, p < 0.001). Bone status was significantly associated with year of study (p = 0.002), physical activity (p < 0.001), carbonated drink intake (p = 0.008), overeating (p = 0.004), and coffee consumption (p = 0.050). Conclusion: Most young medical students had low BMD, with modifiable lifestyle factors contributing significantly highlighting the need for early screening and preventive strategies targeting bone health in this vulnerable population. Limitations include cross-sectional design and gender imbalance.